Nonlinear free vibration analysis of ultra-thin organic solar plates - Nguyen, Nam V.; Nguyen-Xuan, H. (Vietnam Journal of Mechanics, 2025)
Organic photovoltaic devices have gained significant attention as promising solutions to global energy challenges, owing to their unique advantages, including lightweight construction, optical transparency, mechanical flexibility, and low production cost. In this context, the present work aims to introduce an efficient computational approach to investigate the nonlinear free vibration characteristics of ultra-thin organic solar panels. To this end, the solar panel structure is modeled as a multilayered plate, in which each functional layer is assumed to be isotropic. The fundamental displacements are formulated using a refined higher-order shear deformation theory with four independent variables, combined with the von Kármán nonlinear strain assumption to capture large-amplitude effects. The nonlinear natural frequencies are subsequently determined using the non-uniform rational B-splines (NURBS)-based isogeometric analysis (IGA) in conjunction with an iterative displacement-control scheme. Several benchmark investigations are performed to validate the accuracy and robustness of the present formulation. Furthermore, the effect of some key factors, including boundary conditions, length-to-thickness ratios, and aspect dimensions, on the nonlinear vibration characteristics is comprehensively investigated in this work. Several significant remarks can be drawn in order to support the design and optimization of ultra-thin organic solar plate structures in practical engineering applications.